Genomic analysis of Vanessa tameamea, the threatened Hawaiian endemic butterfly, reveals population genetic structure relevant to conservation efforts - Haley E. Arnold; Julian R. Dupuis; Daniel Rubinoff; William P. Haines; Michael San Jose; Renee L. Corpuz; Angela N. Kauwe; Tyler J. Simmonds; Scott M. Geib; Sheina B. Sim (Conservation Genetics, 2025)
Patterns of divergence and speciation on islands have long been of interest in the broader study of evolution. Hawaiʻi’s endemic Kamehameha butterfly ( Vanessa tameamea ) is experiencing population decline, but because of its high vagility and assumed genetic homogeneity as a species, its population structure has not been investigated. To evaluate V. tameamea genetic variation across the Hawaiian Islands, we assembled a reference quality genome assembly for the species using HiFi and HiC reads and performed range-wide population genetic analyses using ddRAD sequencing data. A discriminant analysis of principal components (DAPC) revealed that, contrary to prior assumptions, V. tameamea populations appear to be diverging based on geography, in a pattern similar to other native Hawaiian terrestrial arthropods. Specifically, through demographic history analyses, we find that the distinct population on Kauaʻi is likely to be ancestral, the central islands of Maui, Molokaʻi, and Oʻahu comprise another population, and Hawaiʻi Island forms a third population, with likely more gene exchange with the central islands. Finally, we investigate the SNPs driving differences between groups and find that many are associated with genes that may be relevant to local adaptation to environmental chemicals such as host plant defenses or chemicals introduced by human activity, notably to do with metabolism and detoxification. While much field work remains to investigate any cryptic or phenotypic patterns as well as quantify effective migration, we hope that this work will inform refinement of conservation plans for one of Hawaiʻi’s two native butterflies.

Pre-Hispanic terrace agricultural practices and long-distance transfer of plant taxa in the southern-central Peruvian Andes revealed by phytolith and pollen analysis - Josephine Handley; Nicholas Branch; Frank M. Meddens; Michael Simmonds; José Iriarte (Vegetation History and Archaeobotany, 2024)
The archaeological excavation of two abandoned prehispanic agricultural terraces (Infiernillo and Tocotoccasa) in the Chicha-Soras Valley (Apurimac) in southern-central Peru revealed the presence of palaeosols. The palaeosols represent soil that developed following construction of agricultural terraces during the Middle Horizon. The soil profiles at the current surface developed following reconstruction of the terraces during the Late Intermediate Period. Phytolith analysis revealed an unexpected presence of Arecaceae (palm family) and Marantaceae (arrowroot family) in both terraces, which has been attributed to local cultivation and/or transportation and use of soil, dung, plant material or implements (made of Arecaceae) on the terrace surfaces. Pollen analysis of a nearby wetland (Ayapampa) did not provide evidence for Arecaceae or Marantaceae. Both phytolith and pollen analysis of the terraces and wetland (respectively) indicated that Zea mays was cultivated locally during the Middle Horizon and Late Intermediate Period, although phytoliths of maize are absent from the wetland record during the Middle Horizon. The presence of Solanaceae and Chenopodiaceae/Amaranthaceae pollen in the wetland may be indicative of cultivation of further important taxa during the Middle Horizon and Late Intermediate Period, which continued into the Late Horizon together with Zea mays .

Agricultural systems regulate plant and insect diversity and induce ecosystem novelty - Jessie Woodbridge; Ralph Fyfe; David Smith; Anne de Varielles; Ruth Pelling; Michael J. Grant; Robert Batchelor; Robert Scaife; James Greig; Petra Dark; Denise Druce; Geoff Garbett; et al. (Anthropocene, 2023)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

Additional changes to taxonomy ratified in a special vote by the International Committee on Taxonomy of Viruses (October 2018) - Stuart G. Siddell; Peter J. Walker; Elliot J. Lefkowitz; Arcady R. Mushegian; Michael J. Adams; Bas E. Dutilh; Alexander E. Gorbalenya; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; et al. (Archives of Virology, 2019)

Changes to taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2018) - Andrew M. Q. King; Elliot J. Lefkowitz; Arcady R. Mushegian; Michael J. Adams; Bas E. Dutilh; Alexander E. Gorbalenya; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; et al. (Archives of Virology, 2018)

Changes to taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2017) - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2017)

50 years of the International Committee on Taxonomy of Viruses: progress and prospects - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max L. Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2017)

Ratification vote on taxonomic proposals to the International Committee on Taxonomy of Viruses (2016) - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2016)

A saturated SNP linkage map for the orange wheat blossom midge resistance gene Sm1 - Mulualem T. Kassa; Sabrina Haas; Edgar Schliephake; Clare Lewis; Frank M. You; Curtis J. Pozniak; Ilona Krämer; Dragan Perovic; Andrew G. Sharpe; Pierre R. Fobert; Michael Koch; Ian L. Wise; et al. (Theoretical and Applied Genetics, 2016)

Cardiac electrical conduction, autonomic activity and biomarker release during recovery from prolonged strenuous exercise in trained male cyclists - Glenn M. Stewart; Justin J. Kavanagh; Gus Koerbin; Michael J. Simmonds; Surendran Sabapathy (European Journal of Applied Physiology, 2014)

Caffeine improves supramaximal cycling but not the rate of anaerobic energy release - Michael J. Simmonds; Clare L. Minahan; Surendran Sabapathy (European Journal of Applied Physiology, 2010)

Cytochrome f from the Antarctic psychrophile, Chlamydomonas raudensis UWO 241: structure, sequence, and complementation in the mesophile, Chlamydomonas reinhardtii - Loreta Gudynaite-Savitch; Michael Gretes; Rachael M. Morgan-Kiss; Leonid V. Savitch; John Simmonds; Susanne E. Kohalmi; Norman P. A. Hüner (Molecular Genetics and Genomics, 2006)